(untitled) (KYAMC Journal, 2025)
Background: Dengue, the mosquito born disease has become a public health problem in Bangladesh due to its gradual increase in morbidity and mortality since 2000. In 2023 the country witnessed the worst ever dengue outbreak which covered both urban and rural area. Objective: The study was conducted to assess knowledge regarding dengue and it’s preventive measures among the adult population of Puthia and Paba upazilla upazilla under Rajshahi district. Materials and Methods: This was a cross sectional type of descriptive study which was carried out among rural adult people in Puthia and Paba upazilla under Rajshahi district. The sample size was 364, which was selected purposively. The data were collected from the respondents according to a semi structured questionnaire by face to face interview and then data were analyzed by using SPSS software. Results: Among the 364 respondents majority (53.31%) were in the age group 18-40 years and 50.82% were housewives by occupation. Majority (51.6%) of the respondents possesses insufficient knowledge & 48.4% respondents possess sufficient (> 60% correct answer) knowledge about dengue and its preventive measures. It was found that sufficient knowledge was more among the respondents having higher education which was significant (P<0.05). Conclusion: Dengue is rising in Bangladesh at an alarming rate and extending in the rural area. So everyone should possess proper knowledge and information regarding dengue and it’s prevention otherwise it will make a havoc in Bangladesh.